THE GROWTH AND PROPAGATION OF SYNSEDIMENTARY FAULTS - Childs C.; Nicol A.; Walsh J.J.; Watterson J. (My University, 2003)
Offset of each syn-fault horizon across a synsedimentary (i.e. growth) fault records the throw subsequent to its deposition, allowing successive growth stages of a fault to be determined. This technique has been applied to synsedimentary faults mapped on 3D seismic datasets to distinguish between faults which propagated laterally during growth, faults which did not propagate laterally for significant growth periods and faults in which the lateral dimensions of the active surface decreased during their growth. These different fault tip-line behaviours result in characteristic lateral and dip-parallel fault displacement variations.Fault propagation rates have been measured for 10 fault tips. The maximum propagation rate is 15km/My for gravity driven faults and 3km/My for tectonically driven faults. Rates of fault propagation decrease with elapsed time from the initiation of faulting, with tip-line stasis and retreat becoming dominant in the later stages of fault growth. Static and retreating lateral tip-lines are associated with overlap of the fault strain field with that of a neighbouring fault most often with the formation of a fault relay zone.
Keywords: SYNSEDIMENTARY FAULT; PROPAGATION RATE; TIP-LINE; FAULT GROWTH